The Positive and Negative Aspects of Social media platforms in many Fields, Academic and Non-academic, all over the World in the Digital Era: A Critical Review - Ghafar, Zanyar (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
Social media platforms play a vital role in the modern world, facilitating a variety of activities such as disseminating information, social networking, accessing online resources, advertising, marketing, and education. Businesses benefit from social media platforms, which offer a stable, regular, and speedy platform for various strategies, including internet marketing. The term social media marketing refers to the use of social media websites for promotional objectives. Social media marketing has made it possible for businesses to interact with particular target groups in a quick and effective way. This is a significant advancement for businesses. In addition, there are a number of challenges that social media marketing must conquer in order to operate successfully in the sector. This article will analyse both the good and bad elements of social media branding in the context of the current digital age. The objective of this study is to investigate both of these aspects. The review findings focus on different activities that are not traditional and might be of assistance to students in appropriately dealing with the experiences that they have had throughout their lives.